Banking and Financial Institution Development Economics - Alvaro, Dian (Cattleya Darmaya Fortuna, 2025)
This study examines how the development of financial institutions—measured by the Financial Institution Development (FID) Index,which combines dimensions of depth, access, efficiency, andstability—influences development outcomes at the district/city level.Using a quantitative-causal design, we combine stepwisedifference-in-differences (DiD), macroprudential policy eventstudies, and spatial panel models to capture inter-regionalmechanisms and spillovers. The unit of analysis is a district/citypanel (2016–2024) linked to indicators for banking, fintech, retailpayments, and regional macro variables. Results show thatincreasing FID significantly increases MSME productivity and laborformalization, accompanied by a decrease in non-performing loans(NPLs). Event-study estimates show a flat pre-policy period and astrengthening positive effect 1–3 years post-policy, consistent withlower transaction costs and improved credit screening.Heterogeneity analysis reveals an urban–rural gap: urban areasexperience higher elasticity, while rural areas lag behind on riskadjustedinclusion. Bank-fintech coexistence demonstratesstronger cost discipline effects in competitive markets, whileSharia-dominated regions exhibit good inclusion with relativelymanageable risk profiles. The spatial model indicates meaningfulspillovers, underscoring the importance of cross-districtcoordination (data interoperability, payment corridors, and ashared credit registry). These findings suggest a policy agenda:rural enablement (agents, literacy, shared KYC), bank-fintech dataexchange standards, an adaptive macroprudential frameworkbased on FID, and cross-authority spatial governance to balanceinclusion, intermediation quality, and system resilience